Variability and correlations between agronomic characters in mutant populations of Physalis - dos Santos, Marcio; Henrique Cerutti , Paulo; Tiago dos Santos Carbonari, Luan; Antonio Schwarzer, Pedro; Trevisani , Nicole; Maria Oliveira Pierre Castro, Patrícia; Frederico Guidolin , Altamir (Comunicata Scientiae, 2023)
The physics populations cultivated in Brazil have a restricted genetic base, which makes the genetic progress of the species difficult. A tool available for variant variations is an associated with studies of favorable correlations or cultivar development. The objective was to characterize the variability in characters of was physalis and to obtain estimates of phenotypic correlations between agronomic importance. The gamma treatments were three physalis populations (Colombia, Lages and Fraiburgo), ingredients to irradiation (Co60) in seeds and three exposure times at M0 (0, 250 and 500 Grays). The experimental design used was randomized blocks, with three replications. They were the pH, a titratable total determination (ATT), the total soluble solids (SST), maturation index (IM, SST/ATT), the number of flowers (NDF) and fruits (NFR), the weight of fruits without boll (PDF, in g) and total productivity (PROD in kg ha-1). The results demonstrate that they exist as physical mutant populations when compared to their recognized populations (cultured populations) for the qualitative components (acidity and solids to be evaluated) and not for their proven results. There are positive results between fruits and solid materials, as well as selection it is possible to obtain results with more balanced flavor.